Identical twin cows on winter bluestem pasture used to measure the value of supplemental feed and of Vitamin A - G.A. Greathouse; R.W. Swanson; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1969)
Two pairs of identical twin heifer calves were grazed together on bluestem pasture from 1961 until 1968. During the two winters, 1961-63 each ones daily supplement was 1 pound of ground sorghum grain, 1 pound of soybean oil meal, 20,000 I.U. of Vitamin A and 0.05 lb. of dicalcium phosphate. Salt was always available. The third winter {l963-64}, as bred two year olds, one of each pair was randomly selected to continue receiving the winter supplement, the other to receive only salt and bluestem pasture. They were pastured together, and those fed were separated each morning during the winter to receive the supplement.
Keywords: Cattlemen' s Day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station); 529; Beef; Winter bluestem pasture; Vitamin A; Salt